Balance performance in male and female collegiate basketball athletes: Influence of testing surface - Sabin, M. J.; Ebersole, K. T.; Martindale, A. R.; Price, J. W.; Broglio, S. P. (The Journal of Strength and Conditioning Research, 2010)
The Star Excursion Balance Test (SEBT) is a simple and cost-effective balance test. Information on SEBT performance in athletic populations and under varying testing surfaces is needed to fully elucidate the clinical and training utility of this task. The purpose of this study was to examine SEBT performance in division I, collegiate basketball athletes (men = 9, women = 7) and in a healthy nonathlete control group (men = 7, women = 9). Each participant performed the SEBT with their dominant and nondominant limbs on stable and unstable testing surfaces while reaching in the anterior, medial, and posterior directions. No significant differences resulted between the dominant and nondominant limbs (p > 0.05). Significant differences were found between the basketball and control groups in all directions (p < 0.01) and the average reach score (p < 0.01) with the control group reaching 6-7% farther than the basketball group. A significant main effect for gender (collapsed across group and limb) was present in the posterior direction (p = 0.02). The SEBT performance in the medial and posterior directions and the average score were significantly (p < 0.01) reduced during testing on the unstable surface. These results suggest that athletic status may be a factor to consider when interpreting SEBT reach performance. Future research should examine the influence of SEBT testing in other athletic populations. Further, use of an unstable surface provided a greater challenge to balance. Additional research may provide insight into the role of using an unstable surface with the SEBT as part of an injury risk assessment and its use in identifying limb differences between injured and uninjured limbs.